Intermixing studies in GaN_1−xSb_x highly mismatched alloys - Sarney, Wendy L.; Svensson, Stefan P.; Ting, Min; Segercrantz, Natalie; Walukiewicz, Wladek; Yu, Kin Man; Martin, Robert W.; Novikov, Sergei V.; Foxon, C.T. (Optical Society of America, 2017)
GaN1−xSbx with x~ 5-7% is a highly mismatched alloy predicted to have favorable properties for application as an electrode in a photo-electrochemical cell for solar water splitting. In this study, we grew GaN1−xSbx under conditions intended to induce phase segregation. Prior experiments with the similar alloy GaN1−xAsx, the tendency of Sb to surfact, and the low growth temperatures needed to incorporate Sb, all suggested that GaN1−xSbx alloys would likely exhibit phase segregation. We found that, except for very high Sb compositions, this was not the case, and that instead interdiffusion dominated. Characteristics measured by optical absorption were similar to intentionally grown bulk alloys for the same composition. Furthermore, the alloys produced by this method maintained crystallinity for very high Sb compositions, and allowed higher overall Sb compositions. This method may allow higher temperature growth while still achieving needed Sb compositions for solar water splitting applications.